The NOCTURNE Randomized Trial Comparing 2 Tolvaptan Formulations - Perrone, Ronald D. (Kidney Int Rep, 2020)
INTRODUCTION: Tolvaptan, a treatment for autosomal dominant polycystic kidney disease (ADPKD), inhibits vasopressin V2 receptor signaling, which causes aquaretic adverse events (AAEs). The short-term efficacy and tolerability of a once-daily, modified-release (MR) formulation was assessed relative to the twice-daily, immediate-release (IR) formulation. METHODS: This Phase 2 multicenter, randomized (1:1:1:1), placebo-controlled, double-blind, placebo-masked, parallel-group study (NCT01451827) compared tolvaptan MR 50 mg once daily or tolvaptan MR 80 mg once daily with tolvaptan IR 60/30 mg daily split dose and placebo over 8 weeks in 177 subjects. The primary endpoint was percent change from baseline in total kidney volume (TKV) at week 3. Other endpoints included tolerability, assessed by adverse events and quality of life (QOL) measures. RESULTS: Mean percentage decreases in TKV at week 3 were observed for the pooled group of all (MR+IR) tolvaptan-treated subjects (−2.07%), tolvaptan MR 80 mg (−2.55%), and tolvaptan MR 50 mg (−2.46%) versus placebo (0.09%; P < 0.02 for each comparison with placebo), whereas the decrease with tolvaptan IR 60/30 mg (−1.17%; P = 0.24) did not reach significance. All tolvaptan regimens were associated with AAEs, but scores on ADPKD-specific and generic patient-reported outcome assessments showed little impact based on dosage on overall health-related QOL versus placebo. CONCLUSION: Tolvaptan MR and tolvaptan IR demonstrated similar short-term efficacy, tolerability, and safety, with low impact on multiple measures of QOL. Conclusions regarding long-term efficacy are limited by the short duration of follow-up.